2015
DOI: 10.1002/eji.201545818
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in tissue engineering: The Janus between engraftment and rejection

Abstract: Tissue engineering (TE) for tissue and organ regeneration or replacement is generally performed with scaffold implants, which provide structural and molecular support to in vitro seeded or in vivo recruited cells. TE implants elicit the host immune response, often resulting in engraftment impediment or rejection. Besides this negative effect, however, the immune system components also yield a positive influence on stem cell recruitment and differentiation, allowing tissue regeneration and healing. Thus, a bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 125 publications
(231 reference statements)
2
58
0
Order By: Relevance
“…Scaffold architecture is also reported to significantly affect the host immune response. In particular, highly porous scaffolds seemed to stimulate less severe immune responses to biomaterials probably because they allowed cell infiltrate and the scaffold digestion [48]. In our study, we found that the open structure and the functionalization allowed an increasing infiltration of host cells with time in vivo and a resorption of the hydrogel without generating a severe foreign body reaction.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Scaffold architecture is also reported to significantly affect the host immune response. In particular, highly porous scaffolds seemed to stimulate less severe immune responses to biomaterials probably because they allowed cell infiltrate and the scaffold digestion [48]. In our study, we found that the open structure and the functionalization allowed an increasing infiltration of host cells with time in vivo and a resorption of the hydrogel without generating a severe foreign body reaction.…”
Section: Discussionmentioning
confidence: 57%
“…Engineered tissues elicit the host immune response upon implantation and the balance between inflammation and pro-resolution is essential to determine their rejection or successful engraftment [48]. Therefore, successful tissue and organ regeneration/repair based on engineered construct approaches highly depends on the vascularization dynamics of the implant and the immune response and both need to be tailored to the specific application (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a balanced cooperation between proinflammatory and proresolution players of the immune response is an essential element of implant success. The scaffold, immune, and stem cells are linked by a three-way interaction, and many efforts are being made for scaffold-appropriate design and functionalization in order to drive the inflammation process toward regeneration, vascularization, and implant success (Crupi, Costa, Tarnok, Melzer & Teodori, 2015).…”
Section: Identify Cell To Cell Interaction and The Host Response To Smentioning
confidence: 99%
“…Despite enormous advances in the field of tissue engineering (TE) over the last decade, one of the major issues remains the innate immune response elicited by the scaffold which often leads to fibrosis and eventually failure of the scaffold . For success of TE scaffolds, the latter need to be immune‐tolerant and capable of stimulating stem cell recruitment, proliferation and differentiation …”
Section: Introductionmentioning
confidence: 99%